2013
DOI: 10.1371/journal.pone.0053282
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Intermittent Apnea on Myocardial Tissue Oxygenation—A Study Using Oxygenation-Sensitive Cardiovascular Magnetic Resonance

Abstract: BackgroundCarbon dioxide (CO2) is a recognized vasodilator of myocardial blood vessels that leads to changes in myocardial oxygenation through the recruitment of the coronary flow reserve. Yet, it is unknown whether changes of carbon dioxide induced by breathing maneuvers can be used to modify coronary blood flow and thus myocardial oxygenation. Oxygenation-sensitive cardiovascular magnetic resonance (CMR) using the blood oxygen level-dependent (BOLD) effect allows for non-invasive monitoring of changes of myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
6
27
0
Order By: Relevance
“…Several recent studies have used OS-CMR to monitor changes of myocardial oxygenation after changing blood gas levels, especially O 2 and CO 2 . 3,10,11,30 Those studies showed that OS-CMR is a reliable tool to assess the impact of hyperoxia on myocardial oxygenation. 31 Coronary artery stenosis in our animals was verified by an FFR of <0.75.…”
Section: Downloaded From Hyperoxia Worsens Myocardial Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have used OS-CMR to monitor changes of myocardial oxygenation after changing blood gas levels, especially O 2 and CO 2 . 3,10,11,30 Those studies showed that OS-CMR is a reliable tool to assess the impact of hyperoxia on myocardial oxygenation. 31 Coronary artery stenosis in our animals was verified by an FFR of <0.75.…”
Section: Downloaded From Hyperoxia Worsens Myocardial Ischemiamentioning
confidence: 99%
“…1 Importantly, oxygen and carbon dioxide both have vasoactive properties. Although increased CO 2 levels have vasodilative properties in cerebral and coronary arteries, 2,3 high oxygen tension may have vasoconstricting effects on coronary arteries. 4 If such vasoconstriction would result in a net reduction of blood flow in the territory of a severely stenotic coronary artery, tissue oxygenation may drop.…”
mentioning
confidence: 99%
“…By exploiting the blood oxygenation level-dependent (BOLD) effect [3], T 2 * sensitized CMR has been proposed as a means of assessing myocardial tissue oxygenation and perfusion. T 2 * mapping has been shown to be capable of detecting myocardial ischemia caused by coronary artery stenosis [4], to reveal myocardial perfusion deficits under pharmacological stress [5][6][7][8][9][10], to study endothelial function [11] or to assess breathing maneuver-dependent oxygenation changes in the myocardium [12][13][14][15]. Preclinical studies have also demonstrated the potential of T 2 * mapping to detect structural changes in the infarcted heart muscle and even to distinguish between focal and diffuse fibrosis [16][17][18].…”
Section: T 2 * Sensitized Cardiovascular Magnetic Resonancementioning
confidence: 99%
“…Breathing maneuvers have been proposed as a physiological vasoactive stimulus leading to consistent myocardial signal intensity changes in oxygenation-sensitive MR images [8,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Mostly related to changes in blood carbon dioxide (CO 2 ), a breath-hold (leading to hypercapnia with a net increase of blood CO 2 ) is an effective vasodilator, whereas hyperventilation with hypocapnia causes vasoconstriction [8,[20][21][22]. By combining these maneuvers, the achievable changes in pCO 2 are increased, resulting in a more extended range in vascular resistance with greater changes in OS signal intensity Because of an abnormal coronary vascular response in patients with OSAS, we hypothesized that the coronary vascular response to hyperventilation and long breath-hold is diminished in patients with OSAS when compared to healthy volunteers, as reflected by changes in myocardial oxygenation during voluntary apnea following hyperventilation.…”
Section: Introductionmentioning
confidence: 99%